Determination of zeranol and trenbolone residues in tissue samples of cattle - Firdevs Mor; Fatma Şahindokuyucu; Kürşat Kav; Afşin Köker (Eurasian Journal of Veterinary Sciences)
Aim: In this study, the presence of zeranol and trenbolon in liver, kidney and meat samples marketed in Burdur between January and November in 2009. Materials and Methods: The presence of zeranol and trenbolon was investigated by ELISA in 30 liver, kidney and meat samples obtained from slaughterhouse. Results: Out of 30 liver samples analyzed, 3 (10%) samples had 100-150 ng/kg, 7 samples (23.3%) had 151-200 ng/kg and 19 samples (63.3%) had 201-500 ng/kg zeranol. Out of 30 kidney samples tested, 4 samples (13.3%) had 100- 150 ng/kg, 5 samples (16.6%) had 151-200 ng/kg and 21 samples (70%) had 201-500 ng/kg zeranol. Out of 30 meat samples tested, 4 samples (13.3%) had 100-150 ng/kg, 5 samples (16.6%) had 151-200 ng/kg and 2 samples (6.6%) had had 201-500 ng/kg zeranol. In terms of trenbolon, 1 liver sample (3.3%) carried 100-150 ng/kg, 15 liver samples (50%) carried 151-200 ng/kg and 14 liver samples (46.6%) carried 201-500 ng/kg trenbolon. In kidney samples, 2 of them had 100-150 ng/kg, 4 samples had 151-200 ng/kg and 24 samples had 201-500 ng/kg trenbolon. Three meat samples had 50-100 ng/kg, 21 meat samples had 100-150 ng/kg and 6 samples had 151-200 ng/kg trenbolone. Conclusion: It is stated that levels of zeranol and trenbolone need to be confirmed by confirmation tests and anabolizan levels determined in the study can be hazardous for public health.